The forgotten category of involuntary act (actus involuntarius). The value of involuntary act and its implications in canonical matrimonial law - Dzierżon, Ginter (Ius Matrimoniale, 2025)
In the presented study, the Author’s attention was focused on the category of an involuntary act (actus involuntarius), which is absent in current canonical doctrine. It was, however, the subject of attention of some medieval thinkers (Abelard, St. Thomas). The main research goal of this study is to determine the issue of this category’s implication in the functioning of canonical marital law and the answer to the key question: Does the reference to the category of an involuntary act undermine the theory of a legal act used in marital law? By presenting the achievements of representatives of medical and psychological sciences aho have researched the human brain, the Author demonstrated that the results of research indicate the existence of acts determining human action that remain outside the volitional sphere. In his opinion, however, the assumption of the existence of such acts does not undermine the theory of a legal act. By examining the defects of matrimonial consent which are related to the functioning of reason (simulation, error, lack of the use of reason, lack of discretion of judgment), the Author took the position that, in all of these hypotheses, the lack of will results in the absence of consensus, which is reflected in the absence of marriage (matrimonium inexistens).